ASPEK REPRODUKSI IKAN NILEM (Osteochilus vittatus) YANG DITANGKAP DI SUNGAI WILAYAH MENGWI DAN ABIANSEMAL, KABUPATEN BADUNG, PROVINSI BALI - Rizqi Soviyatul Wahidah; I Wayan Restu; Ni Made Ernawati (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
This study examines the reproductive aspects of Nilem fish (Osteochilus vittatus) in the Mengwi and Abiansemal Rivers, Badung Regency, Bali Province. The parameters analyzed include: length and weight relationship, sex ratio, gonad maturity level (TKG), gonad maturity index (IKG), and fecundity. The study was conducted in the Angantaka Village River, Abiansemal and the River in Abianbase Village in March and May 2025. The research method was quantitative descriptive with a total sample of 100 fish. The results showed: growth patterns were classified as negative allometric (length growth is more dominant than weight), a sex ratio of 3:2, with male fish dominance. Male fish were dominated by TKG I (immature gonads), while female fish were dominated by TKG IV (mature gonads). The highest average IKG value for males was 16.49 and for females 28.35. The average fecundity of female fish at station 1 was 68,732 eggs and at station 2 was 12,812 eggs.